Global assessment of molecularly identified Anisakis Dujardin, 1845 (Nematoda: Anisakidae) in their teleost intermediate hosts - Kuhn, Thomas; Hailer, Frank; Palm, Harry W; Klimpel, Sven (Folia parasitologica, 2013)
Here, we present the ITS ribosomal DNA (rDNA) sequence data on 330 larvae of nematodes of the genus Anisakis Dujardin, 1845 collected from 26 different bony fish species from 21 sampling locations and different climatic zones. New host records are provided for Anisakis simplex (Rudolphi, 1809) sensu stricto (s.s.) and A. pegreffli Campana-Rouget et Biocca, 1955 from Anoplopoma fimbria (Pallas) (Santa Barbara, East Pacific), A. typica (Diesing, 1860) from Caesio cuning (Bloch), Lepturacanthus savala (Cuvier) and Katsuwonus pelamis (Linnaeus) (Indonesia, West Pacific), A. simplex s.s. from Cololabis saira (Brevoort) (Hawaii, Central Pacific), A. simplex C of Nascetti et al. (1986) from Sebastolobus alascanus Bean (Santa Barbara, East Pacific) and A. physeteris Baylis, 1923 from Synaphobranchus kaupii Johnson (Namibia, East Atlantic). Comparison with host records from 60 previous molecular studies of Anisakis species reveals the teleost host range so far recorded for the genus. Perciform (57 species) and gadiform (21) fishes were the most frequently infected orders, followed by pleuronectiforms (15) and scorpaeniforms (15). Most commonly infected fish families were Scombridae (12), Gadidae (10), Carangidae (8) and Clupeidae (7), with Merluccius merluccius (Linnaeus) alone harbouring eight Anisakis species. Different intermediate host compositions implicate differing life cycles for the so far molecularly identified Anisakis sibling species.
Keywords: Animals; Base Sequence; polymerázová řetězová reakce; Polymerase Chain Reaction; nemoci ryb; Molecular Sequence Data; Fish Diseases; Fishes; ryby; mezerníky ribozomální DNA; Host Specificity; Genetic Variation; Anisakis; molekulární sekvence - údaje; DNA, Protozoan; protozoální DNA; anisakióza; sekvence nukleotidů; Sequence Analysis, DNA; Anisakiasis; DNA, Ribosomal Spacer; Larva; zvířata; sekvenční analýza DNA; genetická variace; hostitelská specificita; larva